CSR governance and departmental organization: a typology of best practices. Issue 1 (1st February 2016) - Lock, Irina; Seele, Peter
Abstract : Purpose: This paper aims to study the state of the art of corporate social responsibility (CSR) governance and operational structure within the most sustainable companies to arrive at a typology of CSR organization. Whether companies consider corporate social responsibility (CSR) a strategic management task is mirrored in the department and governance structure of CSR. Design/methodology/approach: By conducting a web content analysis, the authors apply a "best practice" approach to examine the vertical and horizontal organization of CSR within the "most sustainable companies worldwide" (Robeco SAM, 2013). Findings: The results show that most corporations have in place governance structures for CSR that organize it horizontally in stand-alone departments. Three types of CSR organization best practice emerged: the single-headed, two-headed and infused types. Practical implications: The paper indicates three different ways that companies can organize CSR internally. The authors discuss the feasibility of such organization for large and small companies and their day-to-day business. Originality/value: The paper addresses the under-researched area of vertical and horizontal CSR organization at the micro level. The authors analyze the state of the art of organizational and governance structures of CSR in the most sustainable companies and deduce three types of CSR governance and operational architecture.